The Implementation of AI-Powered Chatbots and Virtual Assistants to Assist Students in Solve Math Problems in Real-Time - Rahmah, Alifathu; Novita Zahra (MAXIMA : Jurnal Pendidikan Matematika, 2025)
The implementation of AI in the form of chatbots and virtual assistants has brought significant changes to Mathematics Education. This study aims to analyse the effectiveness of AI-based chatbots and virtual assistants in helping students understand concepts and solve math problems in real-time. Survey results show that most students rate chatbots and virtual assistants as moderately to highly effective, increasing learning motivation and providing ease of access. This technology enables more personalised, interactive, and adaptive learning for students’ needs. Thus, the integration of AI, chatbots, and virtual assistants in Mathematics Education has proven to enhance learning outcomes, motivation, and overall accessibility of education. This study recommends the development and ongoing collaboration between educators and technology developers to optimise benefits in the future.